Terahertz cavity cooling for cuprate superconductors - Denny, S (2015)
Optical cooling is a well-established class of methods for reducing the temperature of a wide variety of atomic, mechanical and condensed matter systems. In this thesis, we demonstrate that it may be possible to cool the fluctuations of the Josephson phase in a cuprate single crystal by the application of coherent terahertz radiation. Such cooling strengthens the superconducting state as measured by switching current distribution, and may lead to an enhancement of the transition temperature Tc We develop a parametric cooling scheme for bilayer cuprates in which intense terahertz driving produces a modulation in the dielectric material properties. This modulates the coupling between interlayer and intralayer Josephson plasmons which we exploit to upconvert thermal fluctuations of the Josephson phase and reduce their effective temperature. We quantify this as the suppression of the fluctuations in both position and momentum quadratures, and additionally via simulated switching current measurements. We predict a reduction in temperature of 30% given realistic material parameters, and identify the cuprates YBCO and TBCCO-2201 as candidate materials in which this effect may be observed experimentally. With a view to developing cavity cooling schemes, we study the coupling between the Josephson modes and the electromagnetic modes of an external cavity. Following a review of the literature, we examine in detail a specific microcavity array geometry which is expected to provide a large coupling through minimisation of the mode volume. Numerical calculations using finite element methods and an effective dielectric model suggest that strong coupling with g / ωp ∼ 0.2 can be achieved using this geometry.